Performances of some high dimensional regression methods - Kurnaz, Fatma Sevinc (TAYLOR & FRANCIS INC, 2021)
Variable selection is one of the important practical issues for many scientific areas, particularly in chemometrics, where data sets include several hundreds of variables and low number of observations. The aim of this paper is to compare some newly proposed variable selection methods by means of extensive simulation studies and to give some practical hints for use of the compared methods. Furthermore, we underpin the performances of compared methods based on real data examples.
Keywords: lasso; L; (1) penalty; Robustness; Variable selection; Mathematics